Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41598-020-72180-7
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of 131I in mice is influenced by circadian variations

Abstract: Effects of radiation and biodistribution of radionuclides are often studied in animal models. Circadian rhythm affects many biological functions and may influence the biokinetics of radionuclides and observed responses. The aim of this study was to investigate if the time during the day of 131I injection affects the biodistribution and absorbed dose to tissues in mice. Biodistribution studies were conducted on male C57BL/6 N mice for three diurnal time-series: the animals were i.v. injected with 160 kBq 131I a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Significantly, one of the main driving forces is the so-called theranostic concept that combines the diagnostic use of one biomarker with a therapeutic option. Some studies have confirmed the value of combined radionuclide PET/CT in neuroendocrine tumors (3), prostate cancer (4), or hematological malignancies (5,6) for the evaluation of efficacy, metastasis, or recurrence monitoring, and some tumors could even be treated with radionuclide-labeled antibodies. Especially, thyroid treatment post-thyroidectomy is the classical protocol where sufficiently large activities of radionuclide 131I are given by mouth to the patient (7); it is still a unique method of cancer treatment (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, one of the main driving forces is the so-called theranostic concept that combines the diagnostic use of one biomarker with a therapeutic option. Some studies have confirmed the value of combined radionuclide PET/CT in neuroendocrine tumors (3), prostate cancer (4), or hematological malignancies (5,6) for the evaluation of efficacy, metastasis, or recurrence monitoring, and some tumors could even be treated with radionuclide-labeled antibodies. Especially, thyroid treatment post-thyroidectomy is the classical protocol where sufficiently large activities of radionuclide 131I are given by mouth to the patient (7); it is still a unique method of cancer treatment (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%